The Attributives Comparison between Chinese and Indonesian - Arini Junaeny (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The word order comparative analysis is important research in linguistics studies. It is assisting the second language learners or teachers in learning process. The research mainly shows the word order in noun phrase. Noun phrase consists of head and attributives, the head is noun and the attributives consist of any type of the word or group of words. The attributives order and the head as a core in noun phrase, it can show similarities and differences structures between Chinese Language and Indonesian Language. This article shows relation between head and attributives order in noun phrase. The order of Chinese Language attributives is placed before the head. The order of Indonesian language attributives (except: number-classifier, negation, restriction word) is placed after the head.